Profiling Potentially Smoke Tainted Red Wines: Volatile Phenols and Aroma Attributes - McKay, M.; Bauer, F.F.; Panzeri, V.; Mokwena, L.; Buica, A. (South African Journal of Enology and Viticulture, 2019)
Malodourous compounds, including volatile phenols (VPs) are frequently found at concentrations below their odour thresholds in wine, and may therefore be considered to present no threat to wine quality. Most investigations into smoke taint quantify compounds by chemical/analytical means, or investigate sensory effects of supra- and peri-threshold contamination in model wine. In this project, twelve wines (submitted by the South African industry as potentially smoke tainted) were screened for VPs using GC-MS, and characterized using descriptive analysis (DA) by a sensory panel highly trained in smoke taint evaluation. Results were compared statistically to elucidate relationships between chemical and sensory characteristics. It was demonstrated, using the combined dataset that concentration and composition of VPs in the wines correlated well with certain sensory attributes. Guaiacol was present in most samples at peri- or suprathreshold levels, but was not correlated with taint unless in combination with other phenols, in which case it was associated with ‘smoky’, ‘ashy’ and ‘herbaceous’ attributes. Wines with supra-threshold levels of VPs showed negative attributes (‘chemical / plastic’, ‘tar / BR’ and ‘medicinal / Elastoplast™’). In some cases, sensory effects (‘earthy / dusty / potato skin’, ‘mouldy / musty’ and ‘cooked vegetables (veg.)’) could not be attributed to supra-threshold VP contamination, and therefore seemed to be due to combinations of VPs at subthreshold levels. Associations between negative attributes and historical bushfire events prior to harvest were found for a number of the wines. This study emphasizes the importance of understanding effects of VPs on wine aroma, and escalating awareness and sensitivity to these issues in the wine industry.